Climate variability impacts on coastal dune slack ecohydrology - Martins, Sara (2019)
The hydrological regime of freshwater systems plays a crucial role in shaping the dynamics of the different biological communities that inhabit them. Climate change is expected to cause major alterations in the hydrological regime of dune slacks by producing shifts in temperature, precipitation and evapotranspiration. Across seasons, we explore the controls on common water fleas (Cladocera) and aquatic plant communities relative to water level regime, water chemistry, weather and geomorphological setting, in a slack of the Sheskinmore dune system, Co. Donegal, northwest Ireland. Cladoceran abundance and diversity peak in summer, but also vary inter-annually, and drivers for this and hydrological variability are discussed. Vegetation is likewise affected by hydrology in a spatial sense, where distribution follows wet/dry patches of water. Water chemistry is more variable within the same season than across different years, particularly related to the drying out of the slack. Rainfall through 2016-2017 was lower than average and evapotranspiration showed higher values than average for the same time period. The influence on the slack of this decreased precipitation extended across successive seasons. The water table is the most important driver of slack ecology, with incidence on biological communities expressed by the increased variability inter-annually, as opposed to seasonal variation.